Cameron, F.R. (2024). Museum Practices and the Posthumanities: Curating for Planetary Habitability. Routledge - White, Nina (Journal of Posthumanism, 2024)
In the nascent field of posthuman museum studies, Fiona R. Cameron cuts a singular figure. Since their conceptualisation of the ‘liquid museum’ in Andrea Witcomb and Kylie Message’s 2015 collection Museum Theory (Cameron, 2015), Cameron has been a crucial driver in theorising and applying posthumanism to the multifarious field of museum governance and practice. Their work navigates and encompasses curatorial documentation practices (Cameron, 2018), digital data and heritage (Cameron, 2021), as well as the museum’s complicity in the conditions of the global Covid19 pandemic (Cameron, 2022). Museum Practices and the Posthumanities: Curating for Planetary Habitability (2024) presents Cameron’s– and indeed, anyone’s– most comprehensive thinking, writing, and action around posthuman museum practices yet.